The Fikih Difabel of Muhammadiyah: context, content, and aspiration to an inclusive Islam - Arif Maftuhin; Abidah Muflihati (IAIN Salatiga, 2022)
Since ratifying the CRPD (Convention on the Rights of Persons with disabilities), Indonesia has witnessed developments in promoting the rights of people with disabilities. Public policies and civil organizations make their respective contributions. Muhammadiyah responded favorably by issuing a comprehensive fatwa on Islam and disability in 2020, compiled in Fikih Difabel. This paper uses an interdisciplinary approach to understand the Fikih Difabel. It explores the historical context of disability in Muhammadiyah and analyzes religious interpretations that become the paradigm and content of Fikih Difabel. Data were collected from various primary sources, such as interviews, observations, and analyses of various Muhammadiyah documents. The research concludes that Fikih Difabel is an organizational and academic effort to find a theological basis to promote disability rights. Fikih Difabel has succeeded in listening to the disabled’s aspirations, integrating the national legal norms and current academic findings, and highlighting Islamic ideals of just and inclusive religion. Fikih Difabel is Muhammadiyah’s contribution to promoting Islam as an inclusive and friendly religion for persons with disabilities